Hubungan Tingkat Depresi pada Fungsi Kognitif pada Lansia di Panti Wreda Salam Sejahtera Kota Bogor - Kaka Maulana; Widayanti; Rizki Perdana (UNISBA Press, 2023)
Abstract. Depression is the most common psychiatric disorder in the elderly worldwide. The incidence of depression in the elderly is often undetected and late-onset forms of depression are strongly associated with cognitive impairment, risk of disease, disability and lower quality of life. This study aims to determine the relationship between the level of elderly depression and cognitive function in the elderly at the Salam Sejahtera Nursing Home, Bogor City in 2022. This study used a cross-sectional method with the Pearson chi-square analysis test with a total of 73 elderly respondents. Cognitive function in this study was assessed using the MMSE (Mini Mental State Examination) and the level of depression using the GDS (Geriatric Depression Scale). Bivariate analysis of this study showed that there were 62 elderly who were not currently experiencing depression with a distribution of 30 elderly having normal cognitive function, 22 having probable cognitive impairment, 10 elderly having definitive cognitive impairment, while there were 11 elderly with possible depression with a distribution of 5 elderly having cognitive function. normal cognitive, 4 elderly people have probable cognitive impairment, and 2 elderly people have definitive cognitive impairment. So that a p value of 0.979 is obtained and it can be concluded that there is no significant relationship between the level of depression and cognitive function. Abstrak. Depresi adalah gangguan psikiatri yang paling sering ditemukan pada usia lanjut di seluruh dunia. Insiden depresi pada usia lanjut sering tidak terdeteksi dan bentuk depresi onset lambat sangat terkait dengan gangguan kognitif, risiko penyakit, kecacatan, dan kualitas hidup yang rendah. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat depresi lansia dengan fungsi kognitif pada lansia di Panti Wreda Salam Sejahtera Kota Bogor tahun 2022. Penelitian ini menggunakan metode cross sectional dengan uji analaisis pearson chi-square dengan total responden sebanyak 73 lansia. Fungsi Kognitif pada penelitian ini dinilai menggunakan MMSE (Mini Mental State Examination) dan tingkat depresi menggunakan GDS (Geriatric Depression Scale). Analisis Bivariat penelitian ini menunjukkan sebanyak 62 lansia yang sedang tidak mengalami depresi dengan distribusi sebanyak 30 lansia memiliki fungsi kognitif normal, 22 memeliki probable gangguan kognitif, 10 lansia memilki definitive gangguan kognitif, sedangkan terdapat 11 lansia dengan kemungkina depresi dengan distribusi sebanyak 5 lansia memiliki fungsi kognitif normal, 4 lansia memiliki probable gangguan kognitif, dan 2 lansia memiliki definitive gangguan kognitif. Sehingga didaptkan nilai p sebesar 0,979 dan dapat disimpulkan bahwa tidak terdapat hubungan signifikan antara tingkat depresi dengan fungsi kognitif.